The Color of Support: The Effect of Sponsor–Team Visual Congruence on Sponsorship Performance. (May 2019) - Henderson, Conor M.; Mazodier, Marc; Sundar, Aparna
Brand sponsorship connects brands with large, passionate audiences. The sponsorship literature emphasizes the importance of brand sponsor–team congruence; however, prior research has largely focused on the relevance of the brand to the sport or geographic area. This article offers the first real-world empirical investigation of the effects of visual congruence through color matching on sponsorship performance. A wide-scale study of 703 Major League Baseball fans' evaluations of their team's sponsors, merged with real stadium signage data, offers evidence of the benefits of visual congruence. Two experiments in the contexts of product packaging and online advertising provide converging evidence of the positive effects of created visual congruence on attitudes toward the sponsorship, brand attitudes, and intentions. Brands without an inherent match to a team can enjoy enhanced sponsorship benefits with little additional costs simply by adopting the team's colors in visual displays. However, the viewer's motivation (fan status), opportunity (fan exposure), and ability (lack of color blindness) to process visual congruence moderates its effectiveness. By using the proposed framework, managers can maximize the value of their sponsorship rights.